Efektivitas Berkumur Seduhan Daun Ungu (Graptophyllum pictum L. Griff) dalam Menurunkan Jumlah Koloni Bakteri Rongga Mulut pada Lansia - Luluk Atuz Zahroh (Fakultas Kedokteran Gigi, 2026)
Background: Bacterial colony is a cluster of bacterial cells visible to the naked eye on a culture medium. The number of bacterial colonies, particularly in the oral cavity of the elderly, continoues to increase in line with physiological conditions and oral hygiene, thereby triggering various oral diseases. Efforts have been made to reduce oral bacteria by utilizing natural ingredients with antibacterial properties, one of which is purple leaf (Graptophyllum pictum L. Griff). The purpose of this study was to determine the effectiveness of rinsing with purple leaf infusion in reducing the number of oral bacterial colonies in the elderly. Method: the study is a laboratory-based experimental study using a pretest-posttest control group design. The study sample consisted of elderly individuals who met the inclusion criteria, totaling 28 participants with each group comprising 7 subjects. The subjects were instructed to rinse their mouths, and their saliva was collected in medicine jars. The sampel were diluted and inoculated onto MHA medium. Colony counter were performed. The data obtained were subsequently analyzed statiscally to determine the differences before and after the treatment. Result: the study showed that group P1 had a result of 177,9 x 10⁵ CFU/ml, K2 had a result of 244,4 x 10⁵ CFU/ml, K- had a result of 77,7 x 10⁵ CFU/ml, and group K+ had a result of 260,1 x 10⁵ CFU/ml. Data analysis using Paired Sampel T-Test showed significance for P1 = 0,014, K2 = 0,011, and group K+ = <0,001, meaning (P<0,05) while for K- = 0,073 meaning it was not significant because (P>0,05). Coclusion: Infusion of purple leaf (Graptophyllum pictum L. Griff) at concentrations of 10% and 20% effectively reduces the number of bacterial colonies in the oral cavity of the elderly, making it a potential alternative to antibacterial mouthwash.
Finalisasi Repo 23 Juni 2026_Yudi
Keywords: bacterial colonies; purple leaves; Graptophyllum pictum L. Griff; elderly; mouthwash; gargling; antibacterial.